Third party insurance? Interactional role alignment in family member mediated primary care consultations - Roberts, Celia; Sarangi, Srikant (Communication and Medicine, 2020)
This paper deals with general practice consultations where there is a third party present, as a companion, to support the patient and act as a mediator between doctor and patient. Our study contrasts with most, but by no means all, of the studies on interpreting, which (1) focus on a transmission of information model in professional interpreting, (2) do not address monolingual mediated consultations where the third person is a carer and/or (3) do not address issues of trust and feelings which can characterise consultations mediated by family members. The data for this paper is drawn from a Londonbased project: Patients with Limited English and Doctors in General Practice: Educational Issues (PLEDGE). Using Goffman’s participant framework and aspects of narrative performance, we propose a cline of mediation, which can be mapped onto the structure of the clinical consultation – as evidenced through two case studies. The analysis indicates that consultations with companions that act as lay interpreters have more in common with monolingual triadic consultations than with professionally interpreted consultations. The shifts in role-relationships and alignments between the three participants subvert their official position to produce a remarkable intimacy and collaboration, while often subduing but sometimes amplifying the patient’s voice. There are implications of our findings both for family carers as mediators and for primary care health providers.